2018
DOI: 10.1002/mnfr.201800263
|View full text |Cite
|
Sign up to set email alerts
|

Diet Enriched with Olive Oil Attenuates Placental Dysfunction in Rats with Gestational Diabetes Induced by Intrauterine Programming

Abstract: Diets enriched with olive oil attenuate placental dysfunction and fetal overgrowth in rats with GDM induced by intrauterine programming.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 44 publications
1
8
0
Order By: Relevance
“…In this study, we focused in the placenta and the putative changes in PPARs expression. Similar to that previously found in a rat model of GDM, 11 we here found that the maternal EVOO‐enriched diet did not prevent the reduced PPARγ levels, but induced anti‐inflammatory effects in the placenta. Indeed, PPAR ligands are provided by the EVOO‐enriched diet, and thus, even without changing PPARγ levels, the activity of this nuclear receptor may be increased, in turn leading to the observed anti‐inflammatory effects 37 .…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…In this study, we focused in the placenta and the putative changes in PPARs expression. Similar to that previously found in a rat model of GDM, 11 we here found that the maternal EVOO‐enriched diet did not prevent the reduced PPARγ levels, but induced anti‐inflammatory effects in the placenta. Indeed, PPAR ligands are provided by the EVOO‐enriched diet, and thus, even without changing PPARγ levels, the activity of this nuclear receptor may be increased, in turn leading to the observed anti‐inflammatory effects 37 .…”
Section: Discussionsupporting
confidence: 88%
“…Our previous studies performed in experimental models of diabetes and pregnancy have shown that a maternal EVOO dietary treatment regulates PPAR pathways and reduces proinflammatory markers in rat embryos, foetuses, placentas and in the offspring's heart 6,11‐13,15 . The dose of olive oil that shows these beneficial effects in animal models of diabetes and pregnancy provides half of the lipid‐derived calories (5% in an 11% lipid content diet).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several polyphenols have been found to exhibit anti‐inflammatory, anti‐obesity, and anti‐diabetic properties; however, there is limited research investigating the impact of polyphenols on GDM. Interestingly, one study showed promising results where supplementing pregnant GDM rats with olive oil, an abundant resource of polyphenols, improved placental dysfunction, however, did not prevent the development of GDM . While the contribution of polyphenols to these effects is unknown, their potential protective effects against GDM warrant investigation.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, one study showed promising results where supplementing pregnant GDM rats with olive oil, an abundant resource of polyphenols, improved placental dysfunction, however, did not prevent the development of GDM. [25] While the contribution of polyphenols to these effects is unknown, their potential protective effects against GDM warrant investigation.…”
Section: Introductionmentioning
confidence: 99%